Geospatial Based Information System Development in Public Administration for Sustainable Development and Planning in Urban Environment - Kouziokas, Georgios N. (European Journal of Sustainable Development, 2016)
It is generally agreed that the governmental authorities should actively encourage the development of an efficient framework of information and communication technology initiatives so as to advance and promote sustainable development and planning strategies. This paper presents a prototype Information System for public administration which was designed to facilitate public management and decision making for sustainable development and planning. The system was developed by using several programming languages and programming tools and also a Database Management System (DBMS) for storing and managing urban data of many kinds. Furthermore, geographic information systems were incorporated into the system in order to make possible to the authorities to deal with issues of spatial nature such as spatial planning. The developed system provides a technology based management of geospatial information, environmental and crime data of urban environment aiming at improving public decision making and also at contributing to a more efficient sustainable development and planning. Keywords: Geographic information systems; Environmental information; Management information system; Public administration; Sustainable development and planning; Urban data.